Cumulative Live Birth Rates Following Insemination With Donor Spermatozoa in Single Women, Same-Sex Couples and Heterosexual Patients. Issue 12 (December 2021) - Linara-Demakakou, Elena; Bodri, Daniel; Wang, Jinjun; Arian-Schad, Mimi; Macklon, Nick; Ahuja, Kamal
Abstract : (Abstracted from Reprod Biomed Online 2020;41:1007–1014) Changes in social attitudes and increasing accessibility of fertility treatment have contributed to an increase in single women and same-sex couples using these services. The majority of the time, these patients are not infertile and favor donor intrauterine insemination (IUI-D), the least invasive and simplest treatment.